RANCANGAN WEBSITE SEJARAH MEMBANGUN NASIONALISME MAHASISWA UNIVERSITAS INTERNSIONAL BATAM SEBAGAI GENERASI MUDA DI ERA GLOBALISASI - Oda I.B Hariyanto; Evi Silvana Muchsinati; Resnika Resnika; Haris Yukie; Viona Angelina; Michelle Michelle; Rio Renaldo Prasena; Thea Evanglista br. Surbakti; Ramadhan Syah Putra; Veronika Desi M.M Panjaitan (National Conference for Community Service Project (NaCosPro), 2020)
The spirit of nationalism and the love of the homeland of the people of Indonesia, especially the younger generation began to fade by the rapid development of science and technology (IPTEK) in the era of globalization. Understanding history has a role and impact on behavior and character on one's identity. Rapid technological advances have had negative impacts such as lifestyle changes that are contrary to the philosophy of the Indonesian state, apathy of the younger generation, the fading of local culture due to the inclusion of foreign cultures, and the lack of interest in studying history which has led to a low sense of nationalism and a sense of patriotism. The solution to building nationalism and the love of the motherland in the younger generation is to instill insight and historical awareness. The purpose of this PKM activity is to increase historical awareness in the younger generation. The research method uses the science and technology diffusion method. The technique of collecting data is done by making a questionnaire through Google form. The data analysis technique is to analyze the percentage of answers from Google forms that have been shared. The results of the survey show that the younger generation at this time is more likely to use gadgets (gadgets) and content in the form of social media applications, blogs, websites, and so on in accordance with the progress of science and technology in the globalization era. Therefore, the historical website called HistoriaPedia is useful for young people to add insight and historical awareness in order to arouse the spirit of nationalism and the love of the country continuously and continuously.